A low-sodium submicron alpha-alumina powder and its preparation method and application
By using organic acids to remove sodium impurities when preparing α-alumina powder, and using magnesium-containing compounds and rare earth oxides to jointly regulate during the calcination stage, a high-purity and low-sodium content submicron α-alumina powder was successfully prepared, which solved the problem of difficult control of the crystal size and equipment pollution in the existing technology, and achieved efficient and environmentally friendly powder preparation.
Patent Information
- Application Number
- CN202211617143.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-15
AI Technical Summary
It is difficult to effectively prepare submicron α-alumina powders with high purity and low sodium content in the prior art. The addition of mineralizers in common methods will lead to the difficulty of controlling the size of the original crystals, and the risk of pollution and corrosion on the production equipment, increasing production costs.
By mixing industrial alumina, organic acid, dispersant and water, adjusting the pH to 7-7.5, and filtration is performed to obtain a low-sodium industrial alumina powder, and mixing it with magnesium-containing compounds and rare earth oxides for calcination, low-sodium submicron α-alumina powder is prepared.
The high purity (99.9~99.99 wt%) and high α-phase content (96~99%) of low-sodium submicron α-alumina powder were achieved, the primary crystal size was 0.3~0.8 μm, the sodium content was low (0.01~0.05 wt%), and no mineralizers such as boron and halides were added, avoiding equipment pollution and cost increase.
Smart Images

Figure CN115974112B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder materials, and in particular to a low-sodium submicron alpha-alumina powder and a preparation method and application thereof. Background Art
[0002] High-purity submicron α-alumina powder has the advantages of stable crystal phase, high hardness, good dimensional stability, etc. It can be widely used in the reinforcement and toughening of various plastics, rubbers, and ceramic products, especially in improving the density, mechanical properties of ceramics and the wear resistance and thermal conductivity of polymer materials. Especially in the preparation of high-performance alumina ceramics, the α-alumina powder used must meet the requirements of high purity, good dispersibility, narrow particle size distribution, small particle size, high activity, and easy sintering.
[0003] At present, there are many methods for preparing α-alumina powder, such as solid phase method, liquid phase method and gas phase method. However, the performance of the prepared powder is not satisfactory. Some methods prepare α-alumina powder with high purity, but its particle size distribution is uneven and the original crystal size is too large. Some methods prepare powder with very fine particle size, but its purity is not high and its dispersibility is poor. Among them, calcination of industrial alumina or aluminum hydroxide is the most commonly used method for preparing α-alumina powder. This method removes sodium impurities by adding mineralizers, and calcines at high temperatures to obtain α-alumina powders of different morphologies and particle sizes. However, the addition of mineralizers makes it difficult to control the original crystals of the powder, and it is difficult to obtain submicron α-alumina powder. In addition, the addition of mineralizers such as boron and halides causes pollution and corrosion to the production equipment, increasing the production cost of α-alumina powder. Therefore, the development of a low-cost, environmentally friendly, low-sodium submicron α-alumina powder preparation method is a hot issue of concern in the industry. Summary of the invention
[0004] The purpose of the present invention is to provide a low-sodium submicron α-alumina powder and a preparation method and application thereof. The low-sodium submicron α-alumina powder prepared by the present invention has low sodium content and high purity, and the original crystal size is submicron level. The process does not add mineralizers such as boron and halides, realizes the controllable growth of the original crystal, does not pollute the production equipment, and is convenient for large-scale production.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing low-sodium submicron α-alumina powder, comprising the following steps:
[0007] Mixing industrial alumina, organic acid, dispersant and water, and adjusting the pH value of the obtained dispersion to 7 to 7.5 to obtain a slurry;
[0008] The slurry is subjected to filter pressing treatment to obtain low-sodium industrial alumina powder;
[0009] The low-sodium industrial alumina powder is mixed with a magnesium-containing compound and a rare earth oxide, and calcined to obtain a low-sodium submicron alpha-alumina powder.
[0010] Preferably, the sodium content of the industrial alumina is 0.35-0.45 wt%.
[0011] Preferably, the organic acid comprises one or more of glacial acetic acid, citric acid, tartaric acid and oxalic acid; the mass of the organic acid is 0.1-3% of the mass of industrial alumina.
[0012] Preferably, the dispersant includes one of ammonium citrate, ammonium polyacrylate, ammonium tartrate and ammonium polyphosphate; the mass of the dispersant is 0.1-1.5% of the mass of industrial alumina.
[0013] Preferably, the sodium content of the low-sodium industrial alumina powder is 0.05-0.1 wt%.
[0014] Preferably, the magnesium-containing compound comprises one of magnesium oxide, magnesium carbonate and magnesium hydroxide; the mass of the magnesium-containing compound is 0.05-0.2% of the mass of the low-sodium industrial alumina powder.
[0015] Preferably, the rare earth oxide includes one of lanthanum oxide, yttrium oxide, cerium oxide and ytterbium oxide; the mass of the rare earth oxide is 0.1-0.3% of the mass of the low-sodium industrial alumina powder.
[0016] Preferably, the calcination temperature is 1100-1300° C., and the holding time is 2-5 hours.
[0017] The present invention provides low-sodium submicron α-alumina powder prepared by the preparation method described in the above technical scheme, with a purity of 99.9-99.99wt%, an α phase content of 96-99%, a primary crystal size of 0.3-0.8μm, and a sodium content of 0.01-0.05wt%.
[0018] The present invention provides the use of the low-sodium submicron α-alumina powder described in the above technical solution in high-performance ceramics, precision polishing or thermal conductive fillers.
[0019] The present invention provides a method for preparing low-sodium submicron α-alumina powder, comprising the following steps: mixing industrial alumina, an organic acid, a dispersant and water, adjusting the pH value of the obtained dispersion to 7-7.5, and obtaining a slurry; performing filter pressing on the slurry to obtain low-sodium industrial alumina powder; mixing the low-sodium industrial alumina powder with a magnesium-containing compound and a rare earth oxide, and calcining to obtain low-sodium submicron α-alumina powder. The low-sodium submicron α-alumina powder prepared by the present invention has a purity of 99.9-99.99wt%, an α phase content of 96-99%, a primary crystal size of 0.3-0.8μm, and a sodium content of 0.01-0.05wt%. The present invention removes sodium impurities through organic acid, and adopts magnesium-containing compounds and rare earth oxides to jointly regulate the original crystal size of alpha-alumina powder in the calcination stage. The prepared low-sodium submicron alpha-alumina powder has low sodium content and high purity, and the original crystal size is submicron level. The process does not add mineralizers such as boron and halides, realizes the controllable growth of original crystals, does not pollute production equipment, and is convenient for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM image of the low-sodium submicron α-alumina powder prepared in Example 2. DETAILED DESCRIPTION
[0021] The present invention provides a method for preparing low-sodium submicron α-alumina powder, comprising the following steps:
[0022] Mixing industrial alumina, organic acid, dispersant and water, and adjusting the pH value of the obtained dispersion to 7 to 7.5 to obtain a slurry;
[0023] The slurry is subjected to filter pressing treatment to obtain low-sodium industrial alumina powder;
[0024] The low-sodium industrial alumina powder is mixed with a magnesium-containing compound and a rare earth oxide, and calcined to obtain a low-sodium submicron alpha-alumina powder.
[0025] The present invention mixes industrial alumina, an organic acid, a dispersant and water, and adjusts the pH value of the obtained dispersion to 7 to 7.5 to obtain a slurry. In the present invention, the water is preferably deionized water. In the present invention, the solid content of the dispersion obtained by mixing the industrial alumina, an organic acid, a dispersant and water is preferably 50 to 80%, more preferably 54 to 70%.
[0026] In the present invention, the sodium content of the industrial alumina is preferably 0.35-0.45 wt %. In the present invention, the particle size of the industrial alumina is preferably 30-80 μm.
[0027] In the present invention, the organic acid preferably includes one or more of glacial acetic acid, citric acid, tartaric acid and oxalic acid; the mass of the organic acid is preferably 0.1-3% of the mass of industrial alumina, more preferably 0.5-2%. In the present invention, the organic acid reacts with the sodium oxide in the industrial alumina to remove the sodium impurity.
[0028] In the present invention, the dispersant preferably includes one of ammonium citrate, ammonium polyacrylate, ammonium tartrate and ammonium polyphosphate; the mass of the dispersant is preferably 0.1-1.5% of the mass of industrial alumina, more preferably 0.5-1%.
[0029] In the present invention, the method for adjusting the pH value of the obtained dispersion to 7 to 7.5 preferably comprises: adding ammonia water to the obtained dispersion and washing with deionized water. In the present invention, the mass concentration of the ammonia water is preferably 5 to 20wt%. In the present invention, the pH value of the dispersion is preferably 2 to 4, more preferably 2.5 to 3.5. In the present invention, the pH value of the slurry is 7 to 7.5, preferably 7.1 to 7.3.
[0030] After obtaining the slurry, the present invention performs filter pressing treatment on the slurry to obtain low-sodium industrial alumina powder. In the present invention, the process parameters of the filter pressing treatment preferably include: pressure 0.5 MPa, pressurization time 30 min. The present invention removes moisture from the slurry through filter pressing treatment.
[0031] In the present invention, the sodium content of the low-sodium industrial alumina powder is preferably 0.05-0.1 wt%, more preferably 0.06-0.08 wt%; the particle size is preferably 30-80 μm.
[0032] After obtaining the low sodium industrial alumina powder, the present invention mixes the low sodium industrial alumina powder with a magnesium-containing compound and a rare earth oxide, and calcines the mixture to obtain low sodium submicron α-alumina powder. In the present invention, the magnesium-containing compound preferably includes one of magnesium oxide, magnesium carbonate and magnesium hydroxide; the mass of the magnesium-containing compound is preferably 0.05-0.2% of the mass of the low sodium industrial alumina powder, and more preferably 0.1-0.2%. In the present invention, the role of the magnesium-containing compound is to control the original crystal size of α-alumina and obtain submicron grains.
[0033] In the present invention, the rare earth oxide preferably includes one of lanthanum oxide, yttrium oxide, cerium oxide and ytterbium oxide; the mass of the rare earth oxide is preferably 0.1-0.3% of the mass of the low-sodium industrial alumina powder, and more preferably 0.2%. In the present invention, the role of the rare earth oxide is to control the original crystal size of α-alumina in combination with the magnesium-containing compound to obtain submicron grains.
[0034] In the present invention, the calcination temperature is preferably 1100-1300°C, more preferably 1150-1250°C; the holding time is preferably 2-5 hours, more preferably 3-4 hours. In the present invention, the calcination atmosphere is air. In the calcination process of the present invention, γ-alumina is converted into α-alumina.
[0035] The present invention provides a low sodium submicron α-alumina powder prepared by the preparation method of the above technical solution, with a purity of 99.9-99.99wt%, an α phase content of 96-99%, a primary crystal size of 0.3-0.8μm, and a sodium content of 0.01-0.05wt%. In the present invention, the α phase content refers to the mass fraction.
[0036] The present invention provides the use of the low-sodium submicron α-alumina powder described in the above technical solution in high-performance ceramics, precision polishing or thermal conductive fillers.
[0037] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] 1 kg of industrial alumina, 1 gram of citric acid, 1 gram of ammonium tartrate and 1 kg of deionized water are mixed to prepare a dispersion, wherein the solid content of the dispersion is 50% and the pH value is 4; ammonia water and deionized water are added to the dispersion for cleaning, and the pH value thereof is adjusted to 7; the obtained slurry is subjected to filter pressing treatment to obtain low-sodium industrial alumina powder with a sodium content of 0.1 wt%;
[0040] 1 kg of the low-sodium industrial alumina powder was mixed with 0.5 g of magnesium oxide and 3 g of yttrium oxide, and calcined in a kiln at 1300°C for 5 hours to obtain low-sodium submicron α-alumina powder with a purity of 99.99wt%, an α-phase content of 99%, a primary crystal size of 0.8μm, and a sodium content of 0.05wt%.
[0041] Example 2
[0042] 1 kg of industrial alumina, 25 g of glacial acetic acid, 5 g of citric acid, 15 g of ammonium citrate and 0.45 kg of deionized water are mixed to prepare a dispersion, wherein the solid content of the dispersion is 80% and the pH value is 2; ammonia water and deionized water are added to the dispersion for cleaning, and the pH value thereof is adjusted to 7; the obtained slurry is subjected to filter pressing treatment to obtain low-sodium industrial alumina powder with a sodium content of 0.05 wt%;
[0043] 1 kg of the low-sodium industrial alumina powder is mixed with 2 g of magnesium oxide and 1 g of lanthanum oxide, and calcined in a kiln at 1100°C for 2 hours to obtain low-sodium submicron α-alumina powder with a purity of 99.9wt%, an α-phase content of 96%, a primary crystal size of 0.3μm, and a sodium content of 0.01wt%.
[0044] Figure 1 This is a SEM image of the low sodium submicron α-alumina powder prepared in Example 2. Figure 1 It can be seen that the original crystals of α-alumina powder are uniform and have a submicron size.
[0045] Example 3
[0046] 1 kg of industrial alumina, 20 g of oxalic acid, 10 g of ammonium polyphosphate and 0.55 kg of deionized water were mixed to prepare a dispersion, wherein the solid content of the dispersion was 64.5% and the pH value was 2.5; ammonia water and deionized water were added to the dispersion for cleaning, and the pH value was adjusted to 7.5; the obtained slurry was subjected to filter pressing to obtain low-sodium industrial alumina powder with a sodium content of 0.06 wt%;
[0047] 1 kg of the low-sodium industrial alumina powder was mixed with 1 gram of magnesium hydroxide and 2 grams of cerium oxide, and calcined in a kiln at 1200°C for 2 hours to obtain low-sodium submicron α-alumina powder with a purity of 99.95wt%, an α-phase content of 98%, a primary crystal size of 0.5μm, and a sodium content of 0.02wt%.
[0048] Example 4
[0049] 1 kg of industrial alumina, 5 g of tartaric acid, 5 g of ammonium polyacrylate and 0.43 kg of deionized water were mixed to prepare a dispersion, wherein the solid content of the dispersion was 70% and the pH value was 3.5; ammonia water and deionized water were added to the dispersion for washing, and the pH value was adjusted to 7.3; the obtained slurry was subjected to filter pressing to obtain low-sodium industrial alumina powder with a sodium content of 0.08 wt%;
[0050] 1 kg of the low-sodium industrial alumina powder was mixed with 1 gram of magnesium hydroxide and 2 grams of cerium oxide, and calcined in a kiln at 1250°C for 3 hours to obtain low-sodium submicron α-alumina powder with a purity of 99.92wt%, an α-phase content of 99%, a primary crystal size of 0.7μm, and a sodium content of 0.04wt%.
[0051] Example 5
[0052] 1 kg of industrial alumina, 8 g of oxalic acid, 2 g of glacial acetic acid, 10 g of ammonium citrate and 0.85 kg of deionized water were mixed to prepare a dispersion, wherein the solid content of the dispersion was 54% and the pH value was 3; ammonia water and deionized water were added to the dispersion for cleaning, and the pH value was adjusted to 7.1; the obtained slurry was subjected to filter pressing to obtain low-sodium industrial alumina powder with a sodium content of 0.07 wt%;
[0053] 1 kg of the low-sodium industrial alumina powder was mixed with 2 g of magnesium hydroxide and 2 g of ytterbium oxide, and calcined in a kiln at 1150°C for 5 hours to obtain low-sodium submicron α-alumina powder with a purity of 99.93wt%, an α-phase content of 97%, a primary crystal size of 0.4μm, and a sodium content of 0.03wt%.
[0054] It can be seen from the above embodiments that the preparation method provided by the present invention is simple, has low synthesis temperature and low cost, and the prepared low-sodium submicron α-alumina powder has high purity, high conversion rate and small original crystal size, and can meet the application requirements of high-performance ceramics, precision polishing and thermal conductive fillers.
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing low-sodium submicron α-alumina powder, comprising the following steps: 1 kg of industrial alumina, 8 g of oxalic acid, 2 g of glacial acetic acid, 10 g of ammonium citrate and 0.85 kg of deionized water were mixed to prepare a dispersion, wherein the solid content of the dispersion was 54% and the pH value was 3; ammonia water and deionized water were added to the dispersion for cleaning, and the pH value was adjusted to 7.1; the obtained slurry was subjected to filter pressing to obtain low-sodium industrial alumina powder with a sodium content of 0.07 wt%; 1 kg of the low-sodium industrial alumina powder was mixed with 2 g of magnesium hydroxide and 2 g of ytterbium oxide, and calcined in a kiln at 1150°C for 5 hours to obtain low-sodium submicron α-alumina powder with a purity of 99.93wt%, an α-phase content of 97%, a primary crystal size of 0.4μm, and a sodium content of 0.03wt%.
2. The low sodium submicron α-alumina powder prepared by the preparation method of claim 1 has a purity of 99.93wt%, an α phase content of 97%, a primary crystal size of 0.4μm, and a sodium content of 0.03wt%.
3. Application of the low sodium submicron α-alumina powder according to claim 2 in high performance ceramics, precision polishing or thermal conductive fillers.
Citation Information
Patent Citations
Doublet aluminum oxide micropowder and preparation method thereof
CN105294138A
Preparation method of low-sodium submicron calcined alumina
CN108675327A